Acting for the camera : back to one - Stone, Peter Allen (Routledge, 2021)
"Acting for the Camera: Back to One is a "how to" book with simple, practical steps to achieve a professional performance on camera. The book focuses on four distinct areas: how to prepare the character and bring them to life, how to execute the technical responsibilities that will assist the editor in creating the on-camera performance in post-production, tips from industry professionals, and how to create effective self-tape auditions. Part One: The Character's World is packed with tools to analyze the script and fully prepare the character before arriving on set. Part Two: The Actor's World focuses on developing technical acting skills for the camera that assist the pre- and post-production teams to create a dynamic on-screen performance. In Part Three: The Professional World industry professionals provide tips from inside the Film/TV audition room and how to navigate a career in the acting business. The final section, Part Four: Self-Tape Like a Pro, outlines how to build a self-tape studio in the privacy of your own home and submit high-quality self-tape auditions that will help you stand out from the competition. Written for students enrolled in Acting for the Camera courses, Acting for the Camera: Back to One explores techniques that can be practiced and mastered by actors of all levels, from the moment they audition for the part through to when they hear that director call "cut!""--